Psychometric properties of the spanish version of the UPPS-P Impulsive Behavior Scale: A rasch rating scale analysis and confirmatory factor analysis - Pilatti, Angelina (2015)
The present study was aimed at determining the psychometric properties of the Spanish version of the UPPS-P Impulsive Behavior Scale in a sample of college students. Participants were 318 college students (36.2% men; mean age = 20.9 years, SD = 6.4 years). The psychometric properties of this Spanish version were analyzed using the Rasch Model and the factor structure was examined using confirmatory factor analysis. The verification of the global fit of the data showed adequate indexes for persons and items. The reliability estimates were high for both items and persons. Differential item functioning across gender was found for 23 items, which likely reflects known differences in impulsivity levels between men and women. The factor structure of the Spanish version of the UPPS-P replicates previous work with the original UPPS-P Scale. Overall, results suggest that test scores from the Spanish version of the UPPS-P show adequate psychometric properties to accurately assess the multidimensional model of impulsivity, which represents the most exhaustive measure of this construct.